Divine aseity and the paradox of divine self-limitation - Antombikums, Aku S. (HTS teologiese studies, 2025)
This article explores the paradox between the classical doctrine of divine aseity and the notion of divine self-limitation. Drawing from biblical narratives and theological concepts such as divine accommodation and kenosis, the article shows that God’s choice to enter into a temporal and relational interaction with creation affects God in such a way that God would not have been affected without the creation. Given the foregoing, open and relational theists conceptualised the notion of divine self-limitation in which, as a result of the creation and human libertarian freedom, God cannot maximally exemplify his great-making properties upheld in traditional theism. I argued in this article that although God seems to become vulnerable because of the act of creation, He nevertheless remains a se because He is not only the source of his existence, but the creation of significant others could not cause God to lose his essential attribute of independence. Therefore, God is still omnipotent, omniscient, eternal, immutable and the like because the possession of these divine attributes does not rule out the possibility that God can enter into a temporal relationship with the creatures. Divine self-limitation predicates real limitations of God contrary to the negating language of the Scripture and, therefore, undermines God’s Almightiness.Contribution: It is argued in this article that although it may be possible to speak about God’s vulnerability because of his act of creation, which seems like a hard choice because He is omniscient, a weaker version of divine aseity that ascribes real limitations to God is not viable.